Determinan Kemiskinan Pada Sepuluh Provinsi di Sumatera Tahun 2015-2021 - Junior Anggara Putra; Arivina Ratih Yulihar; Ukhti Ciptawaty; I Wayan Suparta (CV. Multi Kreasi Media, 2023)
This study aims to analyze the effect of domestic investment, inflation rate, and life expectancy on poverty levels in ten provinces in Sumatra. The method and analysis tool used in this research is panel data regression. The dependent variable used is the poverty rate in ten provinces on the island of Sumatra and the independent variables include domestic investment, inflation rate and life expectancy. The best model obtained is the Fixed Effect Model. The results showed that domestic investment and life expectancy had a negative and significant effect on the poverty rate in the ten provinces in Sumatra, while the inflation rate had a positive and insignificant effect on the poverty rate in the ten provinces in Sumatra.